2019
DOI: 10.1038/s41567-019-0554-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying quantum phase transitions using artificial neural networks on experimental data

Abstract: Machine learning techniques such as artificial neural networks are currently revolutionizing many technological areas and have also proven successful in quantum physics applications. Here we employ an artificial neural network and deep learning techniques to identify quantum phase transitions from single-shot experimental momentum-space density images of ultracold quantum gases and obtain results, which were not feasible with conventional methods. We map out the complete two-dimensional topological phase diagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(146 citation statements)
references
References 53 publications
1
126
0
4
Order By: Relevance
“…Neural network-based machine learning has recently emerged as a powerful technique for learning compact representations of high-dimensional data [10][11][12]. In experimental quantum science, these tools have already been applied profitably to the classification of experimental snapshots [13,14] and qubit readout [15]. The same data-driven approach can be applied to tomographic tasks.…”
mentioning
confidence: 99%
“…Neural network-based machine learning has recently emerged as a powerful technique for learning compact representations of high-dimensional data [10][11][12]. In experimental quantum science, these tools have already been applied profitably to the classification of experimental snapshots [13,14] and qubit readout [15]. The same data-driven approach can be applied to tomographic tasks.…”
mentioning
confidence: 99%
“…此外, 机器学习还被用来 研究量子体系. 例如, 利用人工神经网络识别量子相 变 [16] ; 利用深度神经网络预测和开发量子拓扑材料 [17] , 将机器学习与量子计算相结合进行电子结构计算 [18] , 并且发展了量子机器学习算法以解决量子计算中编码 问题 [19] 等方面的研究. 由此可见 [20,21] 、分子动 力学模拟 [22,23] 以及蒙特卡罗方法.…”
Section: 例如 基于图像识别对肿瘤类型与生长速率进行分unclassified
“…Artificial neural networks (NNs), one of the most efficient and widely used tools of ML [8], are currently at the frontier of research activity. It has been shown that they are capable of predicting phase transitions and critical temperatures [9][10][11][12][13][14][15][16][17][18][19], learning topological indices of quantum phases [20][21][22][23][24][25][26], efficiently representing many-body states [27][28][29][30][31][32][33][34], improving known numerical computational methods [35][36][37], and decoding topological quantum correcting codes [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%